Migration in China: To Work or to Wed? - Arnaud Dupuy (Institute of Labor Economics (IZA), 2018)
This paper develops a model encompassing both Becker's matching model, and Tinbergen-Rosen's hedonic model. We study its properties and provide identification and estimation strategies. Using data on internal migration in China, we estimate the model and compute equilibrium under counter-factual alternatives to decompose the migration surplus. Our findings reveal that about 1/5 of the migration surplus of migrant women is generated in the marriage market and 3/5 in the labor market. We also find that the welfare of urban men married with a migrant wife would have been 10% lower had their migrant wives not entered the urban marriage market.
Keywords: D3; J21; J23; J31; 330; sorting in many local markets; marriage market; hedonic and matching models